Peningkatan hasil belajar marketing melalui model pembelajaran PjBL berbasis media digital: Improving marketing learning outcomes through digital media-based PjBL learning models - Azizah, Euis Rachmawati; Viana, Anisa Okta; Hidayah, Anisa Nur; Safitri, Desy Ayu (Universitas Pamulang, 2023)
This study examines the influence of project-based learning (PjBL) learning model-based digital media on student learning outcomes. This research was conducted on accounting education students in the 2023 class at Semarang State University. This research method uses quantitative methods. The sampling technique uses the population research technique used as the sample in the research. The research population for the 2023 accounting education students class at Semarang State University was 51 people. The data collection technique for this research uses a closed questionnaire. Data analysis techniques include simple linear regression and significance tests (t-tests). The research results show that the application-based PjBL learning model variables positively and significantly influence marketing management learning outcomes for accounting education students at Semarang State University. Abstrak Penelitian ini bertujuan untuk meneliti pengaruh model pembelajaran project based learning (PjBL) berbasis media digital terhadap hasil belajar marketing. Penelitian ini dilakukan pada mahasiswa Pendidikan Akuntansi Angkatan 2023 Universitas Negeri Semarang. Metode penelitian ini menggunakan metode kuantitatif. Teknik pengambilan sampel menggunakan Teknik sampel jenuh. Populasi penelitian mahasiswa Pendidikan Akuntansi Angkatan 2023 Universitas Negeri Semarang sebanyak 51 orang. Teknik Pengumpulan data dari penelitian ini menggunakan Kuesioner Tertutup. Teknik analisis data terdiri: Uji regresi Linier Sederhana, dan Uji Signifikansi (Uji t). Hasil penelitian menunjukkan bahwa terdapat pengaruh positif dan signifikan antara variabel model pembelajaran PjBL berbasis aplikasi terhadap hasil belajar manajemen pemasaran pada mahasiswa pendidikan akuntansi Universitas Negeri Semarang.